Respostas

2013-12-14T20:41:04-02:00
Δ = b² -4ac
Δ = (-7)² -4 *1 * 6
Δ = 49 -24
Δ = 25
x' = (-b + √∆)/ 2a
(-(-7) + 5)/2 * 1
(7 + 5)/2
12/2= 6
x'' = (-b - √∆)/ 2a
(-(-7) - 5)/2 * 1
(7 - 5)/2
2/2= 1

S={6,1}.
2013-12-14T20:46:30-02:00
x²-7x+6=0
-A equação de 2º grau é resolvida por Bhaskara:
a= 1 b= -7 c=6
Δ=b²-4·a·c
Δ=(-7)²-4·1·6
Δ=49-24
Δ=25
-Após achar o valor de delta, temos de encontrar as raízes:
x'= -b +√Δ/2a
x'= -(-7) +√√25/2·1
x'= 7+5/2
x'=12/2
x'= 6

x''= -b - √Δ/2a
x''= -(-7) -√25/2·1
x''= 7-5/2
x''= 2/2
x''= 1

Solução: [1,6]